2020
DOI: 10.1016/j.bjid.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Saliva is a reliable, non-invasive specimen for SARS-CoV-2 detection

Abstract: Background Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the cause of Coronavirus Disease 2019 (COVID-19). Although Real Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR) of respiratory specimens is the gold standard test for detection of SARS-CoV-2 infection, collecting nasopharyngeal swabs causes discomfort to patients and may represent considerable risk for healthcare workers. The use of saliva as a diagnostic sample has several advantages. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 22 publications
6
88
2
4
Order By: Relevance
“…2 provide general information on the selected articles. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 It needs to be clarified that in the studies by Jamal et al and Williams et al T (total number of patients participating in the study) in the meta-analysis and data visualisation is, in fact, the number of the participating patients which were considered in the final analysis for detection of COVID-19. 9 , 14 In addition, due to unclear data on 8 patients in the study by Procop et al, 8 specimens were excluded from the final comparative analysis; therefore, the rest of participating patients were included in the meta-analysis and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 provide general information on the selected articles. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 It needs to be clarified that in the studies by Jamal et al and Williams et al T (total number of patients participating in the study) in the meta-analysis and data visualisation is, in fact, the number of the participating patients which were considered in the final analysis for detection of COVID-19. 9 , 14 In addition, due to unclear data on 8 patients in the study by Procop et al, 8 specimens were excluded from the final comparative analysis; therefore, the rest of participating patients were included in the meta-analysis and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Results of conventional NPS and/or OPS versus saliva samples testing were compared by performing qRT-Real Time PCR assay. 6 There was an overall high agreement (96.1%) between the two tests. In the present study, we detected an overall equivalence between results of qRT-Real Time PCR and Xpert Xpress SARS-CoV-2 assay.…”
mentioning
confidence: 77%
“…Recent studies have shown a high detection rate using saliva/oral fluids as specimens for laboratory detection of SARS-CoV-2. 3 , 4 , 5 , 6 The use of saliva as biological sample has several advantages, such as easy self-collection even at home, and no need of trained personnel for sample collection. In addition, saliva collection is much more comfortable for the patient than NPS or OPS procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, the use of saliva as a less invasive specimen for the detection of SARS-CoV-2 by RT-qPCR has been studied [ 14 , 15 ]. Despite the fact that many studies agree with the similarity of viral detection by PCR in oropharyngeal and nasopharyngeal swabs with saliva [ 16 ], in Mexico, its use as a specimen for the diagnosis of COVID-19 by RT-qPCR is not authorized.…”
Section: What Are Molecular Tests and How Do They Work To Identifymentioning
confidence: 99%